Generation of lumber sawing plan into non-defective pieces by the use of specialized software - Matsyshyn, Yaroslav; Mayevskyy, Volodymyr; Rio, Del (Forestry, Forest, Paper and Woodworking Industry, 2024)
The specialized software for simulation of lumber sawing into non-defective pieces was developed. The suitability of the developed software usage for generation of lumber sawing plan into non-defective pieces was confirmed by the results of performed theoretical and experimental researches.